2012
DOI: 10.7863/jum.2012.31.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Kupffer-Phase Sonazoid-Enhanced Sonography and Hepatobiliary-Phase Gadoxetic Acid-Enhanced Magnetic Resonance Imaging of Hepatocellular Carcinoma and Correlation With Histologic Grading

Abstract: Kupffer-phase Sonazoid-enhanced sonography and hepatobiliary-phase gadoxetic acid-enhanced MRI may be useful in estimating the histologic grade, although Kupffer-phase Sonazoid-enhanced sonography may be more accurate in distinguishing hepatocellular carcinomas, especially moderately and poorly differentiated types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 41 publications
2
54
0
1
Order By: Relevance
“…In addition, knowledge regarding the functional status of hepatocytes makes it possible to differentiate between DN and HCC and between HCC and arterioportal shunts [134][135][136][137][138] and to evaluate hepatic function [139][140][141]. In terms of differential diagnosis of DN and HCC, LGDN shows high signal intensity on hepatobiliary phase images, indicating the presence of functional hepatocytes.…”
Section: Dual Function Agent-perfusion and Hepatocyte Functionmentioning
confidence: 99%
“…In addition, knowledge regarding the functional status of hepatocytes makes it possible to differentiate between DN and HCC and between HCC and arterioportal shunts [134][135][136][137][138] and to evaluate hepatic function [139][140][141]. In terms of differential diagnosis of DN and HCC, LGDN shows high signal intensity on hepatobiliary phase images, indicating the presence of functional hepatocytes.…”
Section: Dual Function Agent-perfusion and Hepatocyte Functionmentioning
confidence: 99%
“…The Kupffer defect is assessed in the Kupffer phase 6-10 min after arterial enhancement of the target nodule. Some investigators have tried to differentiate borderline hepatic nodules using a contrast agent [47,50,51]. According to these studies, although no DNs showed hypoechogenicity in the Kupffer phase, 64-91% of well-differentiated HCCs showed almost complete isoechogenicity.…”
Section: Imaging-based Characterization Of Borderline Hepatic Nodulesmentioning
confidence: 99%
“…It has actually become common to encounter cases where hypervascular HCC or nodule-in-nodule HCC that is undetectable by MDCT is detected in a routine screening by EOB-MRI because of early enhancement in the arterial phase or clear hypointensity in the hepatobiliary phase [11,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,102,103]. Furthermore, studies comparing the diagnostic performance of EOB-MRI and MDCT for hypervascular HCC have shown that EOB-MRI is superior or, at the very l...…”
Section: Diagnostic Algorithmmentioning
confidence: 99%